Dinamika Metodologi Penafsiran Makna Cahaya Ilahi: Studi Komparatif Tafsir Klasik dan Modern terhadap QS. An-Nūr/24: 35 - Ahmad Fannani Ilyasa; M. Mukhid Mashuri; Wiwin Ainish Rohtih (JIQTA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
This research examines the metaphorical meaning of divine light in the Qur'an through the framework of Qur'anic exegesis (tafsir) methodology and Islamic thought to formulate its relevance to the dynamics of modern society's spirituality. Employing a qualitative library-based approach, this study applies comparative analysis techniques (tafsir muqaran) combined with the sociology of knowledge to juxtapose two primary literatures: classical exegesis strictly based on narrations (Ibn Kathir) and modern socio-cultural exegesis (Buya Hamka). The results indicate that the classical exegetical style centers on the consolidation of Islamic theology, positioning pure light as eschatological guidance to preserve the purity of the ummah's faith from the infiltration of foreign thought post-classical civilization crisis. Conversely, the modern approach expands the sacred text into the realm of epistemology and social reality, rendering the verse of light as a philosophical foundation for intellectual awakening, rationality, and the driving force of the Muslim society's movement against colonialism and ignorance. The conclusion of this research affirms that the difference in interpretation demonstrates the richness of Qur'anic exegesis methodology that remains alive (textual living Qur'an) and adapts to respond to the multidimensional crises of its time. Therefore, it is recommended that contemporary Islamic thought should be able to integrate the steadfastness of classical faith with modern critical-transformative power in formulating the Islamic education curriculum.